Modulation of epileptogenesis through transplantation of human mesenchymal stem cells with or without GDNF release - Eliška Waloschková; Esbjörn Melin; Camille Baumlin; My Andersson; Alberto Martínez Serrano; Merab Kokaia; Marco Ledri (Cellular and Molecular Life Sciences)
Abstract Epilepsy is a central nervous system disorder causing uncontrollable seizures. One-third of patients do not respond to current medications, necessitating new treatments. This study targeted epileptogenesis, the process leading to chronic epilepsy, using human mesenchymal stem cells (MSCs) in a rodent model. MSC transplantation can positively affect neurodegenerative diseases by modifying inflammation. Additionally, glial cell line-derived neurotrophic factor (GDNF) may counteract seizures and tissue damage. We transplanted naïve immortalized human adipose-derived MSCs (Ctrl-MSCs) or GDNF-releasing MSCs (GDNF-MSCs, releasing 588.67 ± 20.14 pg/ml/24 h GDNF) into rat hippocampi after kainic acid-induced status epilepticus. Seizure progression was monitored for 5 weeks using video-EEG, behavioral assessments, and histological analysis. Both cell types influenced epileptogenesis. GDNF-MSCs delayed early-stage seizures, while Ctrl-MSCs reduced seizure frequency in later stages. Differences emerged in seizure development and cumulative seizure count, with Ctrl-MSCs showing significant seizure-attenuating effects. Behavioral differences were also noted: Ctrl-MSCs improved short-term memory and reduced anxiety, whereas GDNF-MSCs primarily reduced anxiety without significantly improving memory. This study highlights the therapeutic potential of MSCs, with or without GDNF, in modulating epileptogenesis, offering promising avenues for future clinical treatments.